THE IMPACT OF SOLVENCY POSITION ON BANKS’ PERFORMANCE IN MALAYSIA - Nazaria, Aris; Nur Aina Farihah, Mohd Nasri (UNIMAS Publisher, 2025)
Solvency position reflects a bank’s ability to meet its long-term financial obligations and serves as a key indicator of financial stability and performance. However, there is limited empirical evidence on how different solvency ratios influence bank performance in the Malaysian context. This study aims to examine the impact of solvency position on the performance of commercial banks in Malaysia. A quantitative descriptive research design was employed, covering a five-year period from 2018 to 2023. Secondary data were obtained from the annual reports of firms listed on Bursa Malaysia and analyzed using a panel data regression model via EViews version 12. The findings reveal that both the debt ratio and capital adequacy ratio have a statistically significant effect on return on equity, which serves as a proxy for bank performance. Conversely, the equity ratio does not exhibit a significant impact. Control variables such as bank size and interest rate also show no significant influence on performance. These results offer valuable insights for bank managers, investors, and policymakers, particularly in formulating effective capital management strategies and enhancing financial resilience within the Malaysian banking sector.Keywords:Solvency Position, Equity Ratio, Debt Ratio, Capital Adequacy Ratio, Return on Equity, Bank Performance.